REGULARITIES OF DEVELOPMENT OF COLTS OF THE KAZAKH BACTRIAN BREED - Baimukanov Dastanbek Asylbekovich (Academic Journal of Physical and Chemical Sciences, 2020)
Based on the studies, it was found that for parental couples with a coefficient of wool clip up to 0.8 at the age of one year, the amount of wool clip was 2.4 kg, which is significantly lower by 12.5% compared to herdmates from parents with a coefficient of wool clip of 0.9-1.4, and 29.2% lower in comparison with young oneyear-olds obtained from parental couples with the coefficient of wool clip of 1.5 and above. It was established that the real wool cut was lower in two-year-old females obtained from parents with a coefficient of wool clip of up to 0.8 and 1.5 and higher. In two-year-old females obtained from parental couples with the coefficient of the wool clip of 0.9-1.4, the real wool cut was 9.1% higher than predicted. In the future, during the selection, it is recommended to give preference to individuals with a coefficient of shear of wool 0.9-1.4. In colts of the Kazakh Bactrian of the South Kazakhstan type obtained from female camels corresponding to the technological parameters of dairy productivity, exceeded their mates of the wool-meat direction of productivity in live weight by 17.8% (P<0.01), of the milk and meat direction - in (P <0.1) After weaning, the intensity of growth and development is significantly reduced, which affected the increase in absolute live weight from 6 months to 9 months of age. After weaning, the colts from female camels of dairy productivity, the live weight increased by 11.9%, of the wool and meat productivity - by 34.0%, of the milk and meat direction of productivity - by 23.3%. That is, early weaning is not beneficial for colts from camels of the dairy direction of productivity. From one year to 15 months of age, young livestock from dairy camels have increased live weight by 17.1%, from wool and meat camels - by 19.1%, from milk and meat camels - by 16.6%. From the age of 9 months to 15 months, the colts increased their live weight obtained from mothers with the coefficient of wool clip up to 0.8 by 58.7%, with the coefficient of 0.9-1.4 - by 55.3%, with the coefficient of 1.5 and above - by 91.1 % The height between the humps increases by 15.7% -11.4% -11.7% respectively. That is, all female camels are of wool-meat productivity directions. The effectiveness of conducting assessment and selection by the coefficient of wool clip has been proved in the conditions of Bayserke-Agro LLP.